2(W+4)-3(W+4)=0

Simple and best practice solution for 2(W+4)-3(W+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(W+4)-3(W+4)=0 equation:


Simplifying
2(W + 4) + -3(W + 4) = 0

Reorder the terms:
2(4 + W) + -3(W + 4) = 0
(4 * 2 + W * 2) + -3(W + 4) = 0
(8 + 2W) + -3(W + 4) = 0

Reorder the terms:
8 + 2W + -3(4 + W) = 0
8 + 2W + (4 * -3 + W * -3) = 0
8 + 2W + (-12 + -3W) = 0

Reorder the terms:
8 + -12 + 2W + -3W = 0

Combine like terms: 8 + -12 = -4
-4 + 2W + -3W = 0

Combine like terms: 2W + -3W = -1W
-4 + -1W = 0

Solving
-4 + -1W = 0

Solving for variable 'W'.

Move all terms containing W to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -1W = 0 + 4

Combine like terms: -4 + 4 = 0
0 + -1W = 0 + 4
-1W = 0 + 4

Combine like terms: 0 + 4 = 4
-1W = 4

Divide each side by '-1'.
W = -4

Simplifying
W = -4

See similar equations:

| 6-z=-8 | | X^4-4*x^3+8x= | | y=x^2+1.5xfor-2 | | 2(0)+7y=28 | | y-14=-11 | | 21x+3=17x+15 | | 3t-2=5t+4 | | (7b-1)-2(3b+3)=-2 | | 50x+13=12 | | 3(x^2-5(x+2(3-5x)))= | | 7-z=5 | | 10-6z=-62 | | 21x+3+17x+15=180 | | X^2n-5=11 | | 3-z=-10 | | 10-d=37 | | 12x+1+3*(x+5)=1 | | 90+.5x=50+.9x | | 3cos(6x)sin(5y)=4 | | 4(g+7)=68 | | 2x^2+4x-117=0 | | -4x+5x-8+4=-3x+5-9 | | W-5=-(5-w) | | 64x^2-kx=1 | | 8x^3=64 | | 18x-x+30=0 | | 13d+560m=595 | | 4(2x+7)=-2(x+6)-1 | | 16d+760m=754 | | 1+0.8x+0.6x^2=0 | | (17b-2)-8(2b+3)=-4 | | 8x+4(x+-13)=4 |

Equations solver categories